Crystal structure and electrical properties of Pt/SrBi2Ta2O9/ZrO2/Si - Choi, HS; Kim, EH; Choi, IH; Kim, YT; Choi, JH; Lee, JY (KOREAN PHYSICAL SOC, 2001)
We have investigated the metal-ferroelectric-insulator-semiconductor (MFIS) structure with strontium bismuth tantalate (SBT) as the ferroelectric thin film and ZrO2 as the insulating buffer layer. Sr0.8Bi2.4Ta2O9 thin films were prepared by using the metalorganic decomposition (MOD) method, and ZrO2 films were deposited using rf-sputtering. The memory windows of the MFIS structure were in the range of 0.3 similar to 2.6 V for gate voltages from 3 to 10 V. The maximum memory window was observed in the MFIS with a 28-nm-thick ZrO2 layer. The auger electron spectroscopy (AES) depth profile and high-resolution transmission electron microscopy of the SBT/ZrO2 (28 nm)/Si structure showed that the ZrO2 thin-film buffer layers prevented both the formation of an interfacial layer and interdiffusion between SET and Si.
Keywords: CAPACITORS